Characterization of the complete mitochondrial genome of Okenia hiroi (Baba, 1938) (Nudibranchia, Goniodorididae). Issue 3 (4th March 2021) - Dinh Do, Thinh; Jung, Dae-Wui; Choi, Tae-June; An, Hyung-Eun; Kim, Chang-Bae
Abstract: Okenia is a speciose genus of the family Goniodorididae with more than 50 valid species. The phylogenetic relationships within the genus are little known. The mitogenome is a good marker to understand the phylogenetic relationships of relative species. This study was performed to sequence the mitogenome of O. hiroi . The mitogenome of O. hiroi was 14, 583 bp in size and was composed of 37 genes, including 13 protein-coding genes, two ribosomal RNA genes, and 22 tRNA genes. The nucleotide composition was 30.5% A, 13.6% C, 16.5% G, and 39.4% T. The phylogenetic analysis showed that O. hiroi is sister to Notodoris gardineri (Aegiridae). This study recorded the first mitochondrial genome sequence of the family Goniodorididae.